Znaczenie prawne regulacji dziedzictwa narodowego i dóbr kultury w rozdziale I Konstytucji RP - Frankiewicz, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article examines the issue of national heritage protection in the context of the Polish Constitution. The author points to the impact of specific constitutional provisions on legal acts of lower level. Her views are based on an in-depth analysis of the literature and case-law.
Keywords: ochrona dziedzictwa narodowego; Konstytucja RP; orzecznictwo